Digital Public Leadership dalam Komunikasi Kebijakan Publik Analisis Konten Instagram Bupati Sidenreng Rappang - Abdul Gafur Ibrahim; Yayuk Astuti (Jurnal Administrasi Publik dan Pemerintahan, 2026)
This study employs a qualitative approach using content analysis to examine leadership communication patterns on social media. The unit of analysis consists of 40 Instagram posts published after the regent’s inauguration in 2025. Data were collected through documentation of Instagram posts and analyzed using a coding scheme based on four leadership communication categories: administrative leadership, public service leadership, collaborative governance, and symbolic leadership. The findings show that administrative leadership content dominates the communication pattern with a proportion of 30 percent, followed by public service leadership (25 percent), symbolic leadership (25 percent), and collaborative governance (20 percent). These results indicate that Instagram is mainly used as a platform to display governmental activities and administrative leadership. However, the communication pattern remains largely one-directional, focusing more on information dissemination rather than interactive engagement with citizens. This study contributes to public administration literature by highlighting the role of social media in shaping digital public leadership in local government.